INNOVATIVE ECONOMY AND DIGITAL TRANSFORMATION: NEW OPPORTUNITIES AND CHALLENGES (Лучшие интеллектуальные исследования, 2025)
Annotation. This article explores the theme of “innovative economics and digital transformation: new opportunities and challenges”. The process of digital transformation is leading to fundamental changes in the global economy, which opens up new directions for the development of an innovative economy. The article discusses the impact of digital technology on Business and industry, as well as the need to introduce new economic models and strategies.  The article also addresses the new challenges that arise in the social and economic aspects of digital transformation, specifically in the areas of jobs, education and professional development. Through innovative solutions, opinions are expressed on what strategies should be developed to promote the sustainable development, competitiveness and social well-being of the digital economy.